Plasmids containing insertion elements are potential transposons. - Ohtsubo, E (1980)
We studied in vivo recombination between the plasmid pHS1, a temperature-sensitive replication mutant carrying tetracycline resistance, and pSM1, a small plasmid carrying one copy of the insertion element IS1. Recombinant plasmids were found by selection for tetracycline resistance at 42 degrees C. Their formation was independent of recA function. Analysis of the physical structures of various recombinant DNA molecules with electron microscopy and restriction endonucleases revealed that pSMI was integrated at its IS1 into numerous sites on pHS1, giving rise to a duplication of IS1 in the same orientation at both junctions. Nucleotide sequence analysis of recombinant plasmids and their parental plasmid DNA revealed that nine nucleotides at a target site were duplicated at the junction of each IS1. This phenomenon implies that plasmids containing a translocatable DNA element can be potential transposons.